TINJAUAN PERENCANAAN PERKERASAN LENTUR JALAN RUAS LUBUK SIKAPING - TALU ( P 096 ) - Suharmen Suharmen; Surya Eka Priana; Jon Hafnil; Gusmulyani Gusmulyani (Progressive : Journal of Advanced Engineering and Technology, 2026)
The road is one of the important transportation infrastructure for people's lives. With the construction of this road, it is hoped that it will increase and accelerate the distribution of agricultural, plantation and basic needs for the surrounding community. Road pavement is a construction that is built on a subgrade layer of soil, there are layers of the upper foundation and subbase where each layer consists of compacted aggregates which function to distribute the tension due to the wheel load. There are 3 road pavements, Flexible Pavement, Rigid Pavement, Composite Pavement. Rigid pavement combined with flexible pavement can be in the form of flexible pavement on rigid pavement, or rigid pavement on flexible pavement.To determine the thickness of the flexible pavement, several methods were used, including in this study using the 1987 Bina Marga Component Analysis Method and the 1993 AASTHO Method, the research location for Jalan Lubuk Attitude - Talu.The results of the 1987 Highways Component Analysis Method for new road pavement obtained for the surface layer (D1) which is 10 cm, the upper foundation layer (D2) is 20 cm and the lower layer (D3) is 36.67 cm. And the results of the 1993 AASTHO Pavement Layer method for new road pavements are obtained for the surface layer (D1) 18.86 cm, the top foundation layer (D2) of 19.53 cm and the layerKeywords: Road Pavement, 1987 Bina Marga Component Analysis Method, 1993 AASTHO Method